From Stable PH‐Ylides to α‐Carbanionic Phosphines as Ligands for Zwitterionic Catalysts. Issue 30 (14th June 2022) - Zur, Jana‐Alina; Schmidt, Michelle; Feichtner, Kai‐Stephan; Duari, Prakash; Löffler, Julian; Scherpf, Thorsten; Gessner, Viktoria H.
Abstract: Although ylides are commonly used reagents in organic synthesis, the parent methylphosphine MePH2 only exists in its phosphine form in the condensed phase. Its ylide tautomer H3 P + −CH2 − is considerably higher in energy. Here, we report on the formation of bis(sulfonyl)methyl‐substituted phosphines of the type (RO2 S)2 C(H)−PR2, which form stable PH ylides under ambient conditions, amongst the first examples of an acyclic phosphine which only exists in its PH ylide form. Depending on the exact substitution pattern the phosphines form an equilibrium between the PH ylide and the phosphine form or exist as one of both extremes. These phosphines were found to be ideal starting systems for the facile formation of α‐carbanionic phosphines. The carbanion‐functionalization leads to a switch from electron‐poor to highly electron‐rich phosphines with strong donor abilities and high basicities. Thus, the phosphines readily react with different electrophiles exclusively at the phosphorus atom and not at the carbanionic center. Furthermore, the anionic nature of the phosphines allows the formation of zwitterionic complexes as demonstrated by the isolation of a gold(I) complex with a cationic metal center. The cationic gold center allows for catalytic activity in the hydroamination of alkyne without requiring a further activation step. Abstract : PH ylides such as H2 C=PH3 are considerably higher in energy than their corresponding phosphines H3 C−PH2 . Using bis(sulfonyl)methyl substituents, the first PH ylides stable at ambient conditions could be isolated in solution and in the solid state. They are ideal precursors to carbanionic phosphines with exclusive phosphine reactivity and thus to highly electron‐rich phosphines.